Cidades vacantes, cidades expectantes:produção e transformação dos vazios urbanos em Fortaleza (2000-2018) - Cavalcanti, Emanuel Ramos (2018)
Urban voids have played a relevant role in the debate on contemporary city and urbanism. The academic interest and the solutions offered by urban planning and projects are recent, but they have already been constituted in essential fundamentals and means to address the problem. Its double condition, at the same time ruin and expectation, encourages transformative actions such as urban regeneration and heritage preservation, assigning to those spaces several new uses. The research was based in the city of Fortaleza - capital of Ceará’s State, Brazil - in its former west industrial periphery, result of the industrialization and urban expansion of the late 19th century, which witnessed by the second half of the 20th century the emergence of urban voids from the processes of industrial deconcentration and metropolization. The production and transformation of urban voids is closely related to the dynamics of capitalist production of space that (re) constructs the urban environment from the conditioning factors of capitalist accumulation. However, this logic is market driven and speculative, conflicting with the precepts of the City Statute (2001), which establishes the fundamental principle of the fulfillment of the social function of the city and of urban property. The general objective of this research was to contribute to the discussion of the role of urban voids in the production and transformation of the contemporary in accordance with the conflict between the capitalist production of space and the fulfillment of the social function of the city and of urban property. We defend the thesis that the transformation of the urban voids in Fortaleza, mainly in the period from 2000 to 2018, was mediated by the capitalist production of space, prioritizing market interests instead of fulfilling the social function of the city and of urban property. In the empirical analysis, the Lisbon study, made possible by a mobility doctorate, contributed as an international reference for the Fortaleza analysis. In the Ceará´s capital, we identified and characterized the industrial urban voids of the study area, deepening this analysis with the selection of four cases, relating public and private stakeholders, existing plans and projects with the transformation processes of these spaces.